Ranking Assessment of Renewable Energy Use in the Central and Eastern European Countries - Jarosław BRODNY (Communications of International Proceedings, 2021)
Access to an adequate amount of cheap energy is crucial in the process of achieving the goals of a sustainable economy. The sources from which energy is obtained are also important. Currently, especially in the European Union (EU) countries, a great emphasis is placed on the development of renewable energy (RES), and thus moving away from conventional sources.  Renewable energy is characterized by limited emissions of greenhouse gases and other environmental pollutants, which positively affects the environment. The dynamically developing world economy generates more and more demand for energy, which also causes dynamic development of methods and technologies for RES-based energy. The role, importance and development of these sources have been growing for many years. This dynamic is particularly observed in the EU, including the Central and Eastern European countries (CEE-11). The adopted climate strategies make the development of RES in these countries important for the whole EU. Therefore, it is reasonable to conduct research to assess how the use of energy from the sources in question in the CEE-11 has changed in the recent period (15 years). This paper presents the results of such a study, which aimed to rank the level of RES development in the CEE-11 countries over a 15-year period. This assessment was carried out using the TOPSIS method, which belongs to the MCDM methods group. In addition, the results of the analysis related to the dynamics of change and the coefficient of variation in RES development for the analyzed group of countries are presented. The results make it possible to trace changes and assess the current state of RES development in the CEE-11 countries.
Keywords: Renewable Energy Use; Central And Eastern European Countries; Entropy-TOPSIS Method.